“Jew Yankel”: Three Versions of Dostoevsky’s “Finished Drama” - Viktorovich, Vladimir (Neizvestnyj Dostoevskij, 2024)
Only F. M. Dostoevsky’s brief message speaks about the completion of his play “Jew Yankel” in January 1844. The article formulates three hypotheses/assumptions about the content of the drama. The first correlates the writer’s idea with the literary tradition of portraying a Jewish moneylender, laid down by Shakespeare (“The Merchant of Venice”), Walter Scott (“Ivanhoe”), Pushkin (“The Miserly Knight”) and Gogol (“Taras Bulba”). The humanizing effect of V. Scott’s novel is emphasized. The second version associates Dostoevsky’s Yankel exclusively with the homonymous character from Gogol’s story, first published in 1835. It is proposed to take into account the author’s revision of the story for the 1842 edition, in which Yankel, in the process of building up the epic potential of the work, is endowed with a powerful vital resource and rises to the role of the antagonist of the title character. The third hypothesis refers to the trial of the Jews in the town of Velizh, who were accused of the ritual murder of a Christian child and acquitted many years later. Yankel Aronson died under investigation, which was conducted by inhumane methods. Evidence is provided to confirm that Russian society became aware of these events. The painful end of the Jewish youth could serve as a source of drama, structured with a focus on the writings that made a strong impression on Dostoevsky at that time: “The last day of a man sentenced to death” by V. Hugo and the melodrama “Ugolino” by N. Polevoy. All three versions confirm that pity was not only one of young writer’s motives, but also the ontological basis of his creative universe. The scientific significance of each of the proposed hypotheses also lies in the fact that their deployment allows to expand the understanding of the potential sources of the writer’s work, to reveal an unknown or little-known historical and cultural context of his early, least studied period.